Analisis Sentimen Opini Publik dalam Bahasa Indonesia Terhadap UU Cipta Kerja Menggunakan Naïve Bayes - Alvin Andreas; Yulius Denny Prabowo (UNIVERSITAS KALBIS, 2022)
This study aims to apply the Naïve Bayes method in analyzing public review of the Job Work and measuring the accuracy of Naïve Bayes using twitter dataset. The dataset used in this study was taken from the data text on Twitter social media with 160 tweets. The dataset will be classified into positive sentiments and negative sentiments. The method used in the classification process is the Naïve Bayes method. The software development method used in this research is the Incremental method. The accuracy results obtained during the study were 85% with an average precision, recall, and f1-score of 85%.